MODEL Principal Leadership Model in Strengthening Islamic Education at SDN Mayangan 2 - Alfarizi, Salman; Haris, Abdul; Tobroni (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2025)
The leadership model implemented by a school principal has a major impact on the quality of Islamic education in the school. The aim of this research is to hopefully find a leadership model that is appropriate to the context of Islamic education at SDN Mayangan 2. This research adopts a qualitative approach by utilizing interviews, observation and document analysis as the main methods. The results of this research are that school principals apply four forms of situational leadership models, namely telling, selling, participating, and delegating. The implementation of situational leadership is characterized by the principal's ability to identify school conditions, build a leadership climate, communicate effectively, make timely decisions, carry out ongoing evaluations, and improve the quality of learning and relationships with stakeholders.